Requirements for information technology application competence for Vietnam agro-forestry students in the time of the 4th technology revolution - Toan, Hua Thi; Hai, Trinh Thanh; Kien, Do Trung (Asian Journal of Education and Training, 2024)
The professional work of today’s agricultural and forestry engineers is changing dramatically under the impact of the 4th industrial revolution. In that context, the competence to apply information technology (IT) is one of the core and significant competencies. Therefore, in order for training products to meet the needs of society, one of the problems that training facility for agriculture and forestry industry need to solve is to clearly identify the basic requirements for agro-forestry graduates to meet the basic requirements of IT application competence. Based on theoretical and practical research on the IT application competence of each job position and the trend of employment change in the 4.0 period, the article presents the levels of IT application competence in the agro-forestry industry. On the basis of test results and opinions of experts and employers, the article has proposed the components and required levels of IT application competence for agro-forestry students. The research results, in addition to providing information on the current state of students’ IT application competence, are also a good reference source for agro-forestry training institutions to set learning outcomes, develop training programs, and innovate new training methods to promptly provide high-quality human resources for the agro-forestry industry in the context of the 4th industrial revolution.